2018
DOI: 10.1371/journal.pone.0190358
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously delivered mesenchymal stem cell-derived exosomes target M2-type macrophages in the injured spinal cord

Abstract: In a previous report we showed that intravenous infusion of bone marrow-derived mesenchymal stem cells (MSCs) improved functional recovery after contusive spinal cord injury (SCI) in the non-immunosuppressed rat, although the MSCs themselves were not detected at the spinal cord injury (SCI) site [1]. Rather, the MSCs lodged transiently in the lungs for about two days post-infusion. Preliminary studies and a recent report [2] suggest that the effects of intravenous (IV) infusion of MSCs could be mimicked by IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 63 publications
8
146
3
Order By: Relevance
“…Xiao et al reported that chitinase1 might exert protective effects against Alzheimer's disease by polarizing microglia towards the M2 phenotype [81]. Taking the role of the M2 phenotype with characteristics of anti-inflammation and neuroprotection into consideration, therapeutic treatments that can shift differentiated microglia from the M1 towards the M2 phenotype are encouraged in traumatic neuro-diseases [11,[48][49][50]. In this study, administration of HExos was shown to promote microglial M2 polarization and produce anti-inflammatory cytokines in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al reported that chitinase1 might exert protective effects against Alzheimer's disease by polarizing microglia towards the M2 phenotype [81]. Taking the role of the M2 phenotype with characteristics of anti-inflammation and neuroprotection into consideration, therapeutic treatments that can shift differentiated microglia from the M1 towards the M2 phenotype are encouraged in traumatic neuro-diseases [11,[48][49][50]. In this study, administration of HExos was shown to promote microglial M2 polarization and produce anti-inflammatory cytokines in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hypoxic preconditioning of MSCs can significantly enhance their biological function and activity, thereby improving the transplantation efficacy of MSCs in the treatment of various disease models [46,47]. Although some studies have reported that MSC exosomes could suppress the development of inflammation by shifting the microglia/macrophage phenotype in traumatic CNS diseases [48][49][50], it is still unclear whether MSCs under hypoxic conditions can exert better therapeutic effects to promote SCI functional recovery and whether such enhancement is mediated by exosomal signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in a paper by Xiong et al, intravenously injected CD63 GFP-tagged MSC-exo were found taken up by neurons and astrocytes in traumatic brain injury rat brains [86]. However, a recent study reported that intravenously delivered DiR-labeled MSC-exo were detected predominantly within M2 macrophages, but only a small amount of them localized within astrocytic process endings in contused spinal cord [87]. It shall be noted that in this study, DiR-labeled MSC-exo were infused at one week post-contusion, whereas in our study, PKH26-labeled MSC-exo were infused at 30-min and 1-day post-injury.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 92%
“…Losordo and colleagues demonstrated human CD34+ hematopoietic progenitors generated exosomes in vitro that transferred miR-126-3p to reduce SPRED1 mRNA in murine endothelial cells in vivo, in return enhancing hindlimb revascularization and recovery from ischemia 80 . The secretome of MSC is also known to influence the infiltration hematopoietic cells following tissue injury, including the promotion of a pro-regenerative M2 macrophage differentiation via the transfer of nucleic acid cargo [81][82][83] . Thus, future studies will need to determine whether cargo enriched in EV+ CM can influence the phenotypic and tissue regenerative properties of infiltrating hematopoietic, stromal, or progenitor cells.…”
Section: Discussionmentioning
confidence: 99%